El Género oracular como falsificación en la Literatura Judeo-Helenística y Cristiana - Nieto Ibáñez, Jesús María (Falsificaciones y falsarios de la Literatura Clásica, 2011)
Imitation and forgery of Apollo´s oracles in the Patristic authors with a propagandistic purpose, following the usual practice of Hellenistic Jewish authors with Sibylle, Hystaspes and Apollo himself.